DEFINING POSTMODERN TECHNIQUES FOR DESCRIPTION OF ANNE BOLEYN IN PHILIPPA GREGORY’S NOVEL “THE OTHER BOLEYN GIRL” WITH THE USE OF COMPUTER ALGORITHMS - RIZAYEVA, Dilyayra Shavkatovna (The Lingua Spectrum, 2025)
The paper explores postmodern narrative techniques used by Philippa Gregory in her historical novel The Other Boleyn Girl (2001), focusing particularly on the depiction of Anne Boleyn as a hybridized, fragmented, and ideologically complex character using computational stylistics and text-mining algorithms This research identifies linguistic and thematic patterns that correspond to postmodern literary strategies such as metafiction, intertextuality, and historiographic metafiction. The analysis combines close reading with digital text analytics to quantify Gregory’s stylistic decisions, including lexical frequency, sentiment distribution, and character centrality across the narrative.